Synthesis of carbon nanotube reinforced aluminum composite powder (CNT-Al) by polymer pyrolysis chemical vapor deposition (PP-CVD) coupled high energy ball milling (HEBM) process - Zhang, Yingpeng; Wang, Qun; Ramachandran, Chidambaram Seshadri (Diamond and related materials, 2020)
Carbon nanotube reinforced Aluminum (CNTAl) composite powder was prepared by polymer pyrochemical chemical vapor deposition (PP-CVD) at different temperatures with polyethylene glycol (PEG) as carbon source, cobalt nitrate as catalyst precursor and fine Al powder as starting material. The morphologies, structure, phase composition, and elemental content of the synthesized CNT-Al composite powders were investigated using scanning electron microscopy (SEM), Raman spectroscopy, X-ray diffraction (XRD) and thermo-gravimetric analysis (TGA). The optimized CNT-Al was agglomerated with pure fine Al powder by a high energy ball milling (HEBM) method to obtain several kinds of CNT-Al composite powder with different content of CNTs. The results show that the CNTs in CNT-Al composite powder synthesized at 600 °C showed the highest crystallinity with a reinforcement content of 7 wt%. Although the HEBM process partly smashed the structure of CNTs, it increased the interfacial reaction between CNTs and Al particles. The resulting agglomeration helped to merge the small particulates to form larger particles, thus increasing the overall flowability of the composite powder. Therefore, the PP-CVD coupled HEBM procedure can be employed as an innovative process to prepare the CNT-Al composite powder with uniformly distributed CNTs. The powder manufactured in this investigation has excellent potential to be used in powder metallurgy, cold spraying of CNT-Al composite coatings, and additive manufacturing of composite free-forms. [Display omitted] •A novel preparation process of carbon nanotubes/aluminum composite powder•Temperature optimization for the favorable growth of carbon nanotubes•The lubrication effect of carbon nanotubes in the ball milling process•The evolution of carbon nanotubes structure during ball milling